PENGEMBANGAN MEDIA PEMBELAJARAN SAINS BERBASIS AUGMENTED REALITY MATERI TATA SURYA DI MADRASAH IBTIDAIYAH - Rosyidiana, Hafidz (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2024)
This research describes the characteristics, analyzes the validity, and readability of Augmented Reality-based Science learning media on the solar system. This study is a Research & Development (R&D) study using the Borg & Gall development model. The development was limited to the Development stage. The validity testing of the Augmented Reality-based Science learning media on the solar system was conducted by content experts and media experts using expert validation sheet instruments. The readability testing of the Augmented Reality-based Science media on the solar system development was limited, involving 15 fifth-grade students at MI Ma’arf Mayak Ponorogo using a questionnaire instrument. The research data obtained were analyzed descriptively. The research results show that materi validity was categorized as highly valid with a score of 91,71%, media validity was categorized as highly valid with a score of 88,89% , and product readability was categorized as highly readable with a score of 94%. Based on the results of the validity and readability tests of the Science learning media based on Augmented Reality for the solar system topic, this learning media is suitable for use in the field.